1997
DOI: 10.1016/s0014-5793(97)00747-3
|View full text |Cite
|
Sign up to set email alerts
|

A common core for binding single‐stranded DNA: structural comparison of the single‐stranded DNA‐binding proteins (SSB) from E. coli and human mitochondria

Abstract: The crystal structure of the DNA‐binding domain of E. coli SSB (EcoSSB) has been determined to a resolution of 2.5 Å. This is the first reported structure of a prokaryotic SSB. The structure of the DNA‐binding domain of the E. coli protein is compared to that of the human mitochondrial SSB (HsmtSSB). In spite of the relatively low sequence identity between them, the two proteins display a high degree of structural similarity. EcoSSB crystallises with two dimers in the asymmetric unit, unlike HsmtSSB which cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 39 publications
1
47
0
Order By: Relevance
“…Neither the aminoterminus nor Lys 43 are resolved in either E. coli SSB crystal structures, but their locations suggest that both residues are located in flexible solvent-exposed regions of the protein (Raghunathan et al, 1997;Webster et al, 1997). Such well-exposed locations would yield the high reactivities that we observe for these residues.…”
Section: Fig 6 Amentioning
confidence: 84%
See 3 more Smart Citations
“…Neither the aminoterminus nor Lys 43 are resolved in either E. coli SSB crystal structures, but their locations suggest that both residues are located in flexible solvent-exposed regions of the protein (Raghunathan et al, 1997;Webster et al, 1997). Such well-exposed locations would yield the high reactivities that we observe for these residues.…”
Section: Fig 6 Amentioning
confidence: 84%
“…Lys 49 is not resolved in one E. coli SSB structure (Raghunathan et al, 1997), indicating that it is disordered and probably highly accessible to solvent. In contrast, Lys 49 is resolved in the other E. coli structure (Webster et al, 1997), points toward the ssDNA binding channel, but is still solvent accessible. Both of these structures predict that Lys 49 should be highly reactive, contrary to our observation.…”
Section: Fig 6 Amentioning
confidence: 93%
See 2 more Smart Citations
“…Approximately the first 120 N-terminal residues comprise the OB/SSB fold with conserved structure whereas the rest of the protein has been implicated in interacting with other protein partners and in some cases has been disordered in the crystal structures. Numerous prior efforts have reported in detail the crystal structures of functionally annotated SSBs, [12][13][14][15][16][17][18][19][20][21][22][23] presented comparative analysis of homologous SSBs 20,24 and reported on structures of their protein-DNA complexes. 25,26 An electrophoretic mobility shift assay confirmed that MPN554 binds to a 39-mer single-stranded DNA.…”
mentioning
confidence: 99%